Sarcoidosis after use of interferon for chronic hepatitis C: report of a case and review of the literature - (:unkn) unknown (My University, 2003)
Although interferon has not been classified in the pathogenesis of sarcoidosis, it may rarely lead to this disease during treatment of chronic hepatitis C. The case of a 36-year-old woman with chronic hepatitis C who developed sarcoidosis within 10 weeks of treatment with recombinant interferon-alpha2a and ribavirin is described and all seven similar cases published in English from 1989 to 2001 are discussed.
Keywords: Adult; Female; Humans; Antiviral Agents; Drug Therapy, Combination; Hepatitis C, Chronic; Interferon alpha-2; Interferon-alpha; Recombinant Proteins; Ribavirin; Sarcoidosis, Pulmonary